2017
DOI: 10.1007/s10637-017-0454-z
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of the oral smoothened inhibitor sonidegib in combination with paclitaxel in patients with advanced solid tumors

Abstract: Purpose To establish a recommended phase II dose (RP2D) for the oral smoothened inhibitor sonidegib in combination with paclitaxel; secondary objectives include evaluation of safety, tolerability, markers of Hedgehog (Hh) signaling and preliminary antitumor activity. Methods Patients with advanced solid tumors were enrolled in cohorts of escalating sonidegib dose levels (400mg, 600mg and 800mg orally, once daily on days 1-28) in combination with paclitaxel 80 mg/m on days 1, 8 and 15 in 4-weekly cycles. Dose-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Acquired resistance to sonidegib in a mouse model of MB was associated with mutations in mouse SMO, including N223D, L225R, D388N, S391N, and G457S [84], residues conserved in human SMO (Table 1; Figure 3). Several phase I and II trials for sonidegib in monotherapy and in combination are currently underway in both solid and hematological malignancies [140,141,142,143].…”
Section: Smoothened Inhibitorsmentioning
confidence: 99%
“…Acquired resistance to sonidegib in a mouse model of MB was associated with mutations in mouse SMO, including N223D, L225R, D388N, S391N, and G457S [84], residues conserved in human SMO (Table 1; Figure 3). Several phase I and II trials for sonidegib in monotherapy and in combination are currently underway in both solid and hematological malignancies [140,141,142,143].…”
Section: Smoothened Inhibitorsmentioning
confidence: 99%
“…In a phase I clinical trial (GEICAM/2012-12, EDALINE), three of 12 patients with metastatic TNBC were shown to benefit from the combination therapy of sonidegib and docetaxel, with one patient experiencing a complete response [256,257]. Further phase I trials demonstrated that sonidegib in combination with paclitaxel is well-tolerated and may exert antitumor effects in patients with advanced solid tumors including breast cancer [258]. Similar effects were observed in combination with docetaxel in advanced TNBC patients [256,259].…”
Section: Gpcrs In Breast Cancer: Signaling Biology and Modulatorsmentioning
confidence: 99%
“…However, its antitumor therapeutic performance is reduced by certain issues, such as strong side effects, poor aqueous solubility, and inadequate specificity. [41][42][43] Hence, herein, we generated targeted drug-loaded NBs, namely, PTX-AMD070 NBs, which incorporated AMD070, a small-molecule CXCR4 antagonist, and PTX, a commonly used chemotherapeutic drug. The goal of this study was to study the specific binding of AMD070 and PTX to various tumor cells, targeted ultrasound imaging contrast enhancement, and the therapeutic effect of concurrent use of the NBs with UTND.…”
Section: Discussionmentioning
confidence: 99%